Pre-frontal cortex stimulation by EEG-neurofeedback on food intake behavior in obesity and overweight cases - Naji, Mohammed Isam (2019)
EEG-Neurofeedback is a mode of brain stimulation that is potentially valuable for improving self-regulation skills in cases of behaviours disorder. This study proposed the EEG- neurofeedback can be accompanied by a change in the EEG waves power which that associated with general symptoms of food intake behavior in overweight and obesity cases. The previous studies indicated the personal decision about eating under effect of environment factors such as (visually, smelling, tasting) is related to neural activity of prefrontal lobe of brain. Therefore, there were many attempts made to modify the food intake behavior in overweight and obesity cases through the stimulation of the PreFrontal Cortex (PFC). However, the empirical viewing of EEG- neurofeedback experiments haven't explicated the details about the effect the EEG-NF on the electrical activity of PFC in these cases, it is not yet well explored. This study is cue-exposure EEG-NF experiment constructed into two groups with two conditions (pre-post phases) and two variables types (quantitative and qualitative variables) to verify the hypothesis of effecting the EEG-NF on the electrical activity of PFC and modifying the general symptoms of food intake behavior in excess weight individuals. Twenty-four of excess weight participants (BMI more than 25 kg/m2) were recruited. These participants assigned randomly into two groups; the EX-Group (N=12) who had enrolled in 8 sessions of EEG-NF experiment during the stimulation phase, and the C-Group (N=12) who's had listed in a waiting and not enrolled in EEG-NF experiment The participants provided researchers with a self-report questionnaire relating to their observation of general symptoms of food intake behavior for qualitative analysis, and EEG waves recordings for quantitative analysis into pre and post stimulation phase. The results of two-way analysis of variance (ANOVA) explained that a significant variance in variables between two groups after EEGNF experiment. The quantitative variables indicated the effect of EEG-NF experiment was significant decrement in the mean of whole EEG power from (59.98) to (47.44) dB\Hz and decrement in the mean of Theta\Beta Ratio (TBR) from (2.30) to (1.84). The qualitative variables indicated the effect of EEG-NF experiment which that influenced significantly in changing the median of selfreport questionnaire responses that relating with general symptoms of food intake behavior. The Spearman correlation analysis indicated to significant correlation between these variables at post stimulation phase. The correlation analysis within stimulation phase was explaining more details about the effect of amount of EEG-NF sessions on PFC electrical activity which that indicated to 75% the strength of correlation between TBR and amount of NF sessions. The R2 is 56% of the decrement in TBR can be explained by an increment in EEG-NF sessions, this percentage in an acceptable range to proves the impact of EEG-NF sessions on the TBR for PFC electrical activity that means this manipulating in TBR that influences in improving the food intake behaviours in overweight and obesity cases. This study provides preliminary support for the therapeutic potential of cueexposure EEG-NF experiment that targets the prefrontal cortex, to influence neural processes underlying food intake behavior in overweight and obesity cases.